What is the scientific basis for climate-smart agriculture? - Rosenstock, Todd S.; Lamanna, Christine; Arslan, A.; Richards, Meryl B. (2015)
Climate-smart agriculture (CSA) is a systematic approach to agricultural development. It intends to address climate change and food security challenges simultaneously across levels, from field management to national policy, with goals to 1) improve food security and agricultural productivity, 2) increase the resilience of farming systems to climate change, and 3) mitigate greenhouse gas (GHG) emissions or sequester carbon. After the introduction of the CSA concept in 2010, development organizations, national governments, and donors have quickly adopted a “climate-smart” agenda.